Annihilation of Identity in Heart of Darkness - Pokharel, Bishnu Prasad (Interdisciplinary Journal of Management and Social Sciences, 2023)
Joseph Conrad’s Heart of Darkness portrays the inhabitants of Congo from non-human perceptions. Charles Marlow’s observation and analysis of the citizens of Congo are based on prejudiced viewpoints and pre-defined white archetypes. The chief motive of the Belgians was to justify the native as ferocious and collect the ivory from Congo. Natives did not recognize the worth of tusk while the white men ship it to Europe to brand ornamental articles. This representation of the Congolese annihilates the identity of the native, depicting them as barbaric to accomplish their trade motive. Marlow’s narrative attempts to commodify the natives and display the white people as the embodiment of civilization. Human beings treat non-human behavior to the inhabitant in the designation of civilization. The narrator’s perspective is instrumental to the authorial voice in abolishing the human identity of the people of Congo. His white racial lens constructs the nature and character of the citizens. The general world of the white as represented by Marlow delivers the people of Congo a forceful encyclopaedia of education and civilization. Then develops cultural dominance comprising reason, intelligence, and wisdom. The forceful negation demolishes the real identity of the natives and hence creates a racial verdict. The firm outlook of the white Europeans displays the vivacious demarcation for exploitation. Hence, the text establishes a world of hierarchy among the people living in the same geographical location. The depiction of predisposed attitude and deficit positioning for ivory trading thrashes natives. Such doings cause revolt in the world.